Analysis of β-Catenin Signalling Activity Suggests Differential Regulation of Ontogenetically Distinct Dentate Granule Neuron Populations - Billmann, Charlotte; Schäffner, Iris; Heppt, Jana; Lie, Dieter Chichung (International Journal of Developmental Neuroscience, 2025)
In mammals, the dentate gyrus of the hippocampus is one of the few regions where neurogenesis continues throughout life. As a result, the dentate gyrus harbours neurons of ontogenetically different origin. Notably, ontogenetically different dentate granule neurons (DGNs) are morphologically distinct and fulfil specialized functions in hippocampal information processing and plasticity. Development of adult-born DGNs is tightly controlled by signals released by the complex cellular environment of the adult dentate gyrus. In mice, an adult-like cytoarchitecture of the dentate gyrus is observed only after postnatal Week 2. The question therefore arises when the signalling environment controlling adult neurogenesis is established and whether development of ontogenetically distinct DGNs is subject to the same regulatory pathways. Here, we analyse BATGAL reporter mice to determine the temporal development of β-catenin-signalling activity in the murine DGN lineage. We show that the β-catenin-signalling pattern, which is essential for precise dendritogenesis and neuronal maturation in adulthood, emerges only around 2 weeks after birth and continues to be refined over the next weeks. These results indicate that the signalling environment controlling adult neurogenesis is only gradually established and suggest that the development of ontogenetically distinct DGNs is controlled by different mechanisms.
CRIS-Team Scopus Importer:2025-02-28
Keywords: dentate gyrus; neurogenesis; niche; β-catenin signalling